Strategic Management of Human Resources Development (HR) Lecturer at STAI Al Islahiyah Binjai City - Elfida Santy Hasibuan; Indra Prasetia; Elfrianto Elfrianto (STKIP Taman Siswa Bima, 2024)
This research aims to analyze the strategic management of human resource development for lecturers at STAI Al Islahiyah Binjai. A qualitative approach with analytical methods is this type of research, then data collection efforts are carried out using observation, interviews and documentation methods. The data was declared valid after being tested by data triangulation techniques, and analyzed through the process of data reduction, data display, and drawing conclusions. The results of this research conclude that in quantity the number of lecturers continues to increase (increases) every year. Meanwhile, the weakness is that there are still many lecturers who do not have doctoral qualifications and the number of professors is still small. In the learning aspect, integration-based learning has not yet been realized. Research productivity, publications and community service are also still low. Meanwhile, the challenge currently faced is the demand for the availability of professional and qualified lecturers.